2011
DOI: 10.1007/s11829-011-9128-5
|View full text |Cite
|
Sign up to set email alerts
|

Aphid-host plant interactions: does aphid honeydew exactly reflect the host plant amino acid composition?

Abstract: Plants provide aphids with unbalanced and low concentrations of amino acids. Likely, intracellular symbionts improve the aphid nutrition by participating to the synthesis of essential amino acids. To compare the aphid amino acid uptakes from the host plant and the aphids amino acid excretion into the honeydew, host plant exudates (phloem ? xylem) from infested and uninfested Vicia faba L. plants were compared to the honeydew produced by two aphid species (Acyrthosiphon pisum Harris and Megoura viciae Buckton) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 47 publications
3
50
0
Order By: Relevance
“…Species-specific differences are demonstrable, with aphids on some plants excreting up to 30-70 % melezitose whilst other species of aphid not tended by ants excrete no melezitose (Fischer and Shingelton, 2001). Leroy et al (2011) reported that plant-derived phloem sugars account for 67-89 % of the sugar content of honey dews. Owing to the small volume of exudates available Fischer and Shingleton (2001) could not ascertain the actual content of sugars in aphid honey dew but did report that there were wide differences in the sugar composition of excreta of three species of aphids feeding on two species of poplar and composition depended on whether ants were present.…”
Section: Sugar Intake From Honey Dew Stored In the Hivementioning
confidence: 99%
“…Species-specific differences are demonstrable, with aphids on some plants excreting up to 30-70 % melezitose whilst other species of aphid not tended by ants excrete no melezitose (Fischer and Shingelton, 2001). Leroy et al (2011) reported that plant-derived phloem sugars account for 67-89 % of the sugar content of honey dews. Owing to the small volume of exudates available Fischer and Shingleton (2001) could not ascertain the actual content of sugars in aphid honey dew but did report that there were wide differences in the sugar composition of excreta of three species of aphids feeding on two species of poplar and composition depended on whether ants were present.…”
Section: Sugar Intake From Honey Dew Stored In the Hivementioning
confidence: 99%
“…specific sugars and amino acids) (Heidari & Copland, 1993;Leroy et al, 2011). Many studies have shown that this excretory product acts as an attractant for the adult stage of predators and parasitoids, such as Chrysopidae (McEwen et al, 1993;Petersen & Hunter, 2002), Coccinellidae (Evans & Dixon, 1986;Evans & Richard, 1997), Syrphidae (Budenberg & Powell, 1992;Shonouda, 1996;Bargen et al, 1998;Shonouda et al, 1998a, b;Sutherland et al, 2001) or Aphidiidae (Budenberg, 1990;Budenberg et al, 1992;Du et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing body of examples for symbiotic interactions between insects and bacteria with the associated microorganisms providing nutrients or defensive compounds for their hosts (e.g. Oliver et al 2003Oliver et al , 2005Oliver et al , 2008Oliver et al , 2010Scarborough et al 2005;Douglas 2006;Nakabachi et al 2006;Thao and Baumann 2004;Baumann et al 2002;Kaltenpoth 2009;Schoenian et al 2011;Oh et al 2009aOh et al , b, 2011Brachmann et al 2006;Piel et al 2004;Barke et al 2010;Haeder et al 2009;Scott et al 2008;Leroy et al 2011;Sabri et al 2010) and several examples illustrate pathogenic interactions (e.g. Grenier et al 2006;Ffrench-Constant et al 2007;Herbert and Goodrich-Blair 2007;Lecadet et al 1999;Schnepf et al 1998;de Maagd et al 2003) while the semiochemically mediated interactions are more rarely described.…”
Section: Introductionmentioning
confidence: 99%